Federalism, Public Goods, and Collective Action Issues under Covid-19 - José Angelo Machado (Revista Mexicana de Ciencias Políticas y Sociales)
Taking national defense against Covid-19 as a pure public good, this paper aims to distinguish the risks of collaboration in producing collective action between federations in which central governments coordinated their provision and in which they did not. To do so, it mobilized a model of extensive games model between two local governments to analyze the risks of coordination, disagreement, and defection under both conditions. The resulting propositions were applied to a federation (Brazil) whose central government not only refused to coordinate in addition to trying to prevent subnational governments from reacting to the pandemic, supporting the argument that, in these cases, other federated entities not only dealt with coordination risks, increasing the risks of disagreement (on which measures to adopt) and defection (rushing into the relaxation of non-pharmacological measures). The study is relevant and original in that it offers micro-foundations for collective action problems in federations in which central governments have refused intergovernmental coordination to fight the pandemic, with the challenge of contrasting their arguments in comparative studies that go beyond the present effort based on secondary evidence on a single case.